Implementasi Akad Syariah pada Produk Simpanan dan Pembiayaan di BMT Indragiri Cab. Pekanbaru: Tinjauan Perspektif Keuangan Islam - Arianti; Azwar; Sandrina Ananda Tasya; Roby Hadiansyah; Afira Adila Putri (https://journal.metanusantara.com/jenius/index.php/jem, 2026)
The rapid growth of Islamic financial institutions in Indonesia is still accompanied by a gap between Islamic financial literacy and inclusion. This study employs a field research design with a descriptive qualitative approach. Data were collected through interviews with parties involved in the implementation of savings and financing products to obtain information regarding the application of Islamic contracts in the institutions’ operations. The collected data were then analyzed using an interactive data analysis model. Interactive data analysis involves three stages: data reduction, data presentation, and drawing conclusions or verification. The objective of this study is to analyze the implementation of Sharia contracts in savings and financing products at BMT Indragiri’s Pekanbaru Branch and to assess their compliance with Islamic financial principles. The research findings indicate that the implementation of Sharia contracts for savings and financing products at the Pekanbaru Branch of BMT Indragiri is in accordance with the principles of Islamic finance. Savings products utilize wadiah yad dhamanah, mudharabah, and musyarakah contracts, while financing products utilize murabahah, mudharabah, musyarakah, ijarah, and qardhul hasan contracts. The application of these contracts is carried out clearly, transparently, and based on mutual agreement between both parties, thereby avoiding elements of riba, gharar, and injustice. Additionally, the BMT fulfills its social function through qardhul hasan financing and the collection of social funds to assist the community. However, this study also found that public understanding of Sharia contracts still needs to be improved through more intensive outreach and education.